Chromosomal aberrations in primary amenorrhea: A retrospective study - Seema Korgaonkar; Somprakash Dhangar; Vinayak Kulkarni; Lily Kerketta; Babu Rao Vundinti (Wolters Kluwer Medknow Publications, 2019)
Objectives: The aim of this study was to estimate the frequency of chromosomal abnormalities and establish the association with clinical of factors such as secondary sexual characters and gonad development in primary amenorrhea (PA). Study Design: The study was carried out in a large cohort of PA. The chromosomal aberrations were correlated with secondary sexual characters and anatomical abnormalities. Materials and Methods: The data of 490 cases of PA were collected retrospectively. The chromosomal preparations were done from the peripheral blood and subjected to giemsa-trypsin-giemsa banding and karyotyped according to the International System of Human Cytogenetic Nomenclature 2013. The fluorescence in situ hybridization was carried out using centromeric and whole painting probes for X and Y chromosome. Statistical Analysis: Statistical analysis of the data was performed using online version of social science statistics software. Results: A high frequency of abnormal uterus (81.9%) and ovaries (86.7%) were detected in our study. A total of 121 (24.7%) cases were identified with abnormal karyotype. The numerical chromosomal abnormalities were identified in 53 (43.8%) cases while structural abnormalities were identified in 32 (26.4%) cases. The XY karyotype was detected in 29.8% females with PA. The PA individuals with anatomical abnormalities (84.3%) had a high frequency (24.6%) of chromosomal aberrations. Conclusions: The present study concluded that cytogenetics plays an important role in precise diagnosis which helps in the management of PA. The cytogenetic analysis should be carried out to know the genetic basis of PA.